Convective-radiative heat transfer in a rotating square cavity with a local heat-generating source. (July 2018) - Mikhailenko, S.A.; Sheremet, M.A.; Mohamad, A.A.
Highlights: Convective heat transfer combined with surface thermal radiation within a rotating square cavity having a local heat-generating and heat-conducting source is analyzed numerically. Governing equations have been solved by finite difference method. Effects of surface emissivity, Taylor number, and Ostrogradsky number on fluid flow and heat transfer are studied. A growth of the Taylor number results in the heat transfer enhancement for the moderate rotation intensity. Abstract: Development of passive cooling systems for electronic devices demands the multiparametric analysis of main heat transfer mechanisms inside the domains with heat-generating elements. Such analysis can allow to find optimal parameters for the heated elements in order to decrease the working temperature of these elements. Nowadays many electronic units are mounted in rotating systems. The present work is devoted to numerical investigation of convective-radiative heat transfer in a rotating square cavity with a local heat-generating and heat-conducting source. The considered cavity has horizontal adiabatic walls, isothermal cooled vertical borders and a heat-generating element located on the bottom wall. Mathematical model formulated in non-dimensional stream function, vorticity and temperature have been solved by finite difference method. The influence of surface emissivity, Taylor number, and Ostrogradsky number on streamlines, isotherms, average Nusselt number, fluid flow rate and average temperature inside the heater have been studied. The heat transfer enhancement with rotation for moderate values of the Taylor number has been shown. It has been found that in the case of heat-generating and heat-conducting element the periodicity in fluid flow intensity and heat transfer rates can be obtained after a lot of complete revolutions. A growth of the surface emissivity can essentially reduce the average temperature inside the heated element, while an intensive rotation also allows to decrease this temperature. Graphical abstract: